Involving Physicians in Upstream Conversations: The Serious Illness Communication Checklist. Issue 2 (1st June 2012) - Block, S
Abstract : Background: Early discussion of end-of-life issues has been found to be associated with better quality of life, reduced use of aggressive care, earlier hospice referral, improved bereavement outcomes for survivors, and reduced costs. Yet, such conversations do not occur regularly for patients with serious illness. Barriers to such conversations are found in patients, physicians, and the health care system. In this presentation, we will review data about the benefits of early discussions, describe the rationale for the use of a checklist to improve discussions of end-of-life issues, describe appropriate "triggers" for such conversations, and review risks and benefits of early discussions. Based on an extensive development process we will propose an evidence-based Serious Illness Communication Checklist (SICC) that is designed to guide early clinician discussions with patients and their families about values and goals about end-of-life care, review a training program for physicians and other clinicians to prepare them to use the SICC, and describe a system-wide approach for communicating patient values and goals through use of a structured format within the electronic medical record. Finally, preliminary impressions from the early phases of a prospective, cluster randomized trial in oncology will be described.